Reception of Progressive Rock in Rolling Stone Magazine in the Period 1969-1979 - Borek, Jan (Musicologica Olomucensia, 2020)
This text presents an analysis of contemporary critical reception of progressive rock in Rolling Stone magazine in the years 1969-1979. The findings are subsequently compared with the common popular music history narrative in the form of the so-called punk discourse. A new classification of progressive rock sub-styles is introduced for the purpose of demonstrating varying attitudes of contemporary critical reception toward various stylistic families of the broader progressive rock genre in the 1970s, proposing also new Czech nomenclature.
Keywords: progressive rock; Rolling Stone; popular music; popular culture; music criticism; rock criticism